A Literary Analysis of the Books of Proverbs and Ecclesiastes (2012)
There have been efforts at research into biblical literature, particularly from the sociohistorical and doctrinal perspectives. However, little attention has been given to the literary and stylistic analysis of the Bible. The devotion to the sacredness of the biblical text has short-circuited the needed attention to a proper literary critique of the narrative. This study therefore is a close critique that foregrounds the literariness of the Bible with particular reference to the King James Version of the Books of Proverbs and Ecclesiastes. Thus, the study goes beyond the works of scholars like Alter, Kermode, Norton, Damrosch, Gardiner, and others which have only focused on biblical intertextuality, theological and sociohistorical interpretations of the Bible. Literary stylistic approach from the perspective of Formalism and New Criticism was adopted for this study. This approach was used to examine the stylistic resources, literary forms and functions of the selected texts within the framework of the Bible as a literary piece. The Books of Proverbs and Ecclesiastes draw upon a knowledge of philosophy, history, orature, sociology and culture. The literary stylistic approach proved an effective way of making the Proverbs and Ecclesiastes meaningful to their users and also established the credibility and relevance of literary biblical studies as different from doctrinal biblical studies. The development of a literary theory such as Bible as literature, Formalism and New Criticism, enable us to look at the Bible from the perspective of its literary elements. Instead of emphasising the Bible solely as a sacred text, this study enables us to acknowledge it as a literary text with literary features. There are recurrent patterns in the theme, imagery, structure and style of the selected texts. The figurative devices employed advance the persuasiveness of the style. Without ignoring their essentially religious contexts, the study shows the conscious literary framework that shapes meaning and interpretation in Proverbs and Ecclesiastes and intensifies their degree of literary appreciation. The study extends the frontiers of extrinsic literary criticism. It has implications for scholars and teachers of literature, religion and culture, who are strategic, not only in situating literary studies within the context of moral instructions, but also in locating biblical values within literary texts. The use of the literary perspective enables the two books to be viewed against the socio-cultural background of the society, from which they emerged, thereby providing a more rounded appreciation of their contents. Literature thus has distinctive characteristics that make a literary approach to the Bible a worthwhile scholarly venture